Morphological and genetic variation among different isolates of Magnaporthe grisea collected from Chhattisgarh - S.K. PARIDA, S. CHAND and A. KOTASTHANE, H. SONAH*, R.K. DESHMUKH, (Indian Phytopathology, 2009)
Rice blast caused by Magnaporthe grisea has been recognized as the most serious disease, causing epidemic worldwide. The fungal pathogen is capable of infecting many grass species but individual isolate exhibit a limited host range. There are several features that make M. grisea an ideal subject for genomic studies. In present study, 30 monosporic blast cultures were isolated from rice cultivars and grasses from different areas of Chattisgarh. One of the blast pathogen was isolated from banana which is the first report in India. Variability studies on M. grisea were carried out following morphological as well as molecular markers analysis. The lesion morphology varied on different hosts, coalescing lesions on the host tissue. Variation in individual spores and culture morphology was observed. Despite apparent clonality in M. grisea, a high level of genetic variability was observed through PCR based RAPD analysis of M. grisea from different non-rice and rice hosts. A total of 131 polymorphic markers were scored using 16 selected random decamer primers. The similarity degree value for the isolates ranged from 0.51 to 0.89. Cluster analysis reveals, isolates from same location grouped together regardless of whether they were isolated from rice or grass.